A novel cutting tool design to avoid surface damage in bone machining - Liao, Zhirong; Axinte, Dragos A.; Gao, Dong (Elsevier, 2017)
With its anisotropic structure, bone machining occurs as shear/serrated cutting mechanisms at low values of uncut chip thickness while at high values it results in fracture cutting mechanisms which lead to significant tissues damages; hence, utilising conventional tools at high material removal rates comes with drawback on surface damages, situation that needs to be avoided. This paper reports on a novel design of a milling cutter which includes on the back of main cutting edge a succession of micro-cutting edges arranged on an Archimedes spiral that allows the limitation of surface damage. That is, by adjusting the feed rate, this tool design allows the change of the cutting mechanism as follows: (i) “shear/serrated” cutting mode: when the feed rate is smaller than a pre-established threshold, only the main cutting edges work which yields a shear/serrated cutting mechanism; (ii) combined “fracture & shear” cutting mode occurring at high feed rate caused by: the main cutting edges working in fracture cutting mechanism while the subsequent micro-cutting edges work under shear cutting mechanism, combination which leads to significant reduction of bone surface damages. This new tool concept was materialised on a solid diamond composite, characterised by excellent heat conduction and low wear rates. Cutting experiments with various values of feed rates showed that the proposed tool designed concept significantly reduced the fracture damage of bone cut surface as well as cutting temperature compared with the dimensionally equivalently conventional tool.